THE IMPACT OF FINANCIAL TECHNOLOGY ON THE DEVELOPMENT OF FINANCIAL INCLUSION ON MSME - Arie Pratania Putri; Vincent Tiovandy; Jovita Zefanya Stephanie Kawijaya; Rhonetta Sandy (JRAK, 2022)
This research aims at determining the impact of financial technology on the development of financial inclusion on MSMEs in North Sumatera. The authors took sample by using of one of the perpetrator's economies, namely SMEs in North Sumatra. The 100 samples taken in this research, only 85% of MSMEs met the requirements in the eligibility test. The results contained in this research are a description of 85 MSMEs believed to reflect the utility of fintech itself and how it developed. In this research, the authors used the analysis of multiple linear regression using SPSS. The variables of P2P Lending and Cashless Society have a significant positive effect on financial inclusion, while Risk and Investment Market Provisioning have no significant effect on financial inclusion.